5
$\begingroup$

Is it trivial to say $$\mathop {\lim }\limits_{n \to \infty } {(1 + {k \over n})^n} = e^{k},$$

considering the fact that we know $$\mathop {\lim }\limits_{n \to \infty } {(1 + {1 \over n})^n} = e?$$

$\endgroup$
5
  • 4
    $\begingroup$ The first limit is $e^k$. $\endgroup$
    – user63181
    Nov 15, 2013 at 15:30
  • 1
    $\begingroup$ can you tell me why? $\endgroup$ Nov 15, 2013 at 15:33
  • 3
    $\begingroup$ $\lim\limits_{n \to \infty } {\left(1 + \frac{k}{n}\right)^n} = \lim\limits_{n \to \infty } {(( 1 + \frac{1}{\frac{n}{k}})^{\frac{n}{k}}})^k=e^k$ $\endgroup$
    – user35603
    Nov 15, 2013 at 15:36
  • 1
    $\begingroup$ oh, got it. please write it as an answer $\endgroup$ Nov 15, 2013 at 15:37
  • $\begingroup$ please, fix the OP $e\to e^k$ $\endgroup$
    – Ilya
    Nov 15, 2013 at 15:49

3 Answers 3

9
$\begingroup$

Since $\frac kn = \frac 1 {\frac nk}$ and $n = \frac nk \cdot k$ we have $$\lim_{n\to \infty} (1+\frac kn)^n = \lim_{n\to\infty} \left( (1 + \frac{1}{\frac nk})^{\frac nk} \right)^k = \left ( \lim_{u\to\infty} (1+\frac 1u)^u \right)^k = e^k$$ If $k<0$, you have $$(1+\frac 1u)^{-u} = \left((1+\frac 1u)^u\right)^{-1} \to e^{-1} \qquad (u\to\infty)$$

$\endgroup$
2
  • 3
    $\begingroup$ That's fine for $k > 0$. But the statement is actually true for all $k$. $\endgroup$ Nov 15, 2013 at 15:42
  • $\begingroup$ @RobertIsrael Your assertion is correct, thanks.# $\endgroup$
    – AlexR
    Nov 15, 2013 at 15:45
2
$\begingroup$

Well, by (one) definition of $e$, we have $$e=\lim_{t\to\infty}\left(1+\frac1t\right)^t.$$ Now, in particular, if $k>0$, then letting $t=\frac nk,$ we find that $t\to\infty$ precisely as $n\to\infty,$ so that $$\begin{align}\lim_{n\to\infty}\left(1+\frac kn\right)^n &= \lim_{n\to\infty}\left(1+\frac kn\right)^{\frac nk\cdot k}\\ &= \lim_{t\to\infty}\left(1+\frac1t\right)^{tk}\\ &= \lim_{t\to\infty}\left(\left(1+\frac1t\right)^t\right)^k\\ &= \left(\lim_{t\to\infty}\left(1+\frac1t\right)^t\right)^k\\ &= e^k\end{align}$$ The $k=0$ case is trivial. To deal with the $k<0$ case, observe that $$1+\frac kn=\frac{n+k}{n}=\left(\frac{n}{n+k}\right)^{-1}=\left(1+\frac{-k}{n+k}\right)^{-1},$$ so letting $t=\frac{n+k}{-k},$ we once again have $t\to\infty$ as $n\to\infty,$ and so $$\begin{align}\lim_{n\to\infty}\left(1+\frac kn\right)^n &= \lim_{n\to\infty}\left(1+\frac{-k}{n+k}\right)^{-n}\\ &= \lim_{n\to\infty}\left(1+\frac{-k}{n+k}\right)^{-(n+k)+k}\\ &= \lim_{n\to\infty}\left(1+\frac{-k}{n+k}\right)^{-(n+k)}\left(1+\frac{-k}{n+k}\right)^k\\ &= \lim_{n\to\infty}\left(1+\frac{-k}{n+k}\right)^{-(n+k)}\lim_{n\to\infty}\left(1+\frac{-k}{n+k}\right)^k\\ &= \lim_{n\to\infty}\left(1+\frac kn\right)^{\frac{n+k}{-k}\cdot k}\\ &= \lim_{t\to\infty}\left(1+\frac1t\right)^{tk}\\ &= \lim_{t\to\infty}\left(\left(1+\frac1t\right)^t\right)^k\\ &= \left(\lim_{t\to\infty}\left(1+\frac1t\right)^t\right)^k\\ &= e^k\end{align}$$

$\endgroup$
-1
$\begingroup$

By $\displaystyle\lim_{n\to\infty}\left(1+\frac{1}{n}\right)^n = e,n\in\mathbb{N}$, we have $$\lim_{x\to\infty}\left(1+\frac{1}{x}\right)^x = e,\quad x\in \mathbb{R}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.